Enhancing immunotherapy efficacy in colorectal cancer: targeting the FGR-AKT-SP1-DKK1 axis with DCC-2036 (Rebastinib) - Xiguang Chen; Qiting Zeng; Liyang Yin; Bingru Yan; Chen Wu; Jianbo Feng; Ying Wu; Jun He; Wenjun Ding; Jing Zhong; Yingying Shen; Xuyu Zu (Cell Death and Disease)
Abstract This research demonstrates that DCC-2036 (Rebastinib), a potent third-generation tyrosine kinase inhibitor (TKI), effectively suppresses tumor growth in colorectal cancer (CRC) models with functional immune systems. The findings underscore the capacity of DCC-2036 to enhance both the activation and cytotoxic functionality of CD8+ T cells, which are crucial for facilitating anti-tumor immune responses. Through comprehensive multi-omics investigations, significant shifts in both gene and protein expression profiles were detected, notably a marked decrease in DKK1 levels. This reduction in DKK1 was linked to diminished CD8+ T cell effectiveness, correlating with decreased FGR expression. Moreover, our findings identify FGR as a pivotal modulator that influences DKK1 expression via the PI3K-AKT-SP1 signaling cascade. Correlative analysis of clinical specimens supports the experimental data, showing that increased levels of FGR and DKK1 in CRC tissues are associated with inferior clinical outcomes and reduced efficacy of immunotherapeutic interventions. Consequently, targeting the FGR-AKT-SP1-DKK1 pathway with DCC-2036 could potentiate immunotherapy by enhancing CD8+ T cell functionality and their tumor infiltration. This strategy may contribute significantly to the refinement of therapeutic approaches for CRC, potentially improving patient prognoses.